Pendidikan Karakter pada Kurikulum 2013 dan Perkembangannya Menuju Profil Pelajar Pancasila - Gunarti Sukriyatun (Primer Edukasi Journal, 2022)
This study aims to: 1) Knowing the functions and objectives of character education, 2) Knowing the implementation of character education in the 2013 curriculum, and 3) Knowing the current development of character education. This study uses a descriptive qualitative approach through a literature study. The results of the study indicate that character education has a function as a developer, improvement and filter for the dignity of the nation. Character education in the 2013 Curriculum prioritizes character education that forms intelligent and characterful people. Character values are sourced from religion, Pancasila, culture and national education goals. Character education was developed with the Mental Revolution program with the policy of Strengthening Character Education followed by the Pancasila Student Program.